SEMANTIC ANALYSIS OF TASTE-EXPRESSING UNITS IN ENGLISH PROVERBS - Toshmatova Muxlisa (Bright Mind Publishing, 2025)
This paper investigates the semantic features of taste-related expressions used in English proverbs. By examining lexical units associated with sensory taste—such as sweetness, bitterness, sourness, saltiness, and sharpness—the study reveals how these expressions extend beyond literal meanings to convey moral evaluations, emotional states, and cultural values. Using a corpus of 120 proverbs and applying cognitive-semantic analysis, the research identifies recurring conceptual metaphors including Good Is Sweet, Bad Is Bitter, and Wisdom Is Salt. The findings demonstrate that taste vocabulary functions as a powerful semantic and cultural tool for shaping worldview through proverbs.
Keywords: Taste metaphors; English proverbs; semantic analysis; sweetness; bitterness; sourness; salt; conceptual metaphor; cognitive semantics; figurative language; paremiology.